(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
The whitefly Bemisia tabaci (Gennadius) is one of the most important pests worldwide for its direct damage and above all due to its role as vector of more than 100 plant viruses. In Italy it is one of the factors presently limiting protected vegetable crops, especially in southern regions, where three different biotypes (B, Q and T) occur. The results are reported in the present paper of a molecular investigation carried out in Sicily on presence and distribution of these biotypes, during a 5 years period. The study, based on analysis of 40 populations sampled on both cultivated and ornamental or wild plants, evidenced the wider occurrence of biotype B in the island, though with a general trend towards a larger diffusion of biotype Q.